The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7150/jca.63635
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated C4orf19 confers poor prognosis in colon adenocarcinoma identified by gene co-expression network

Abstract: Colon adenocarcinoma (COAD) is the most common histologic subtype of colorectal cancer (CRC), and its prognosis is poor. Unlike traditional research in molecular biology, which is limited to analyzing the function of a single gene or protein in malignant tumors. The Weighted gene correlation network analysis (WGCNA) technique is used to describe the gene association model among different samples in order to identify highly collaborative genes. In this study, a computational strategy was used to conduct a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…For example, in Fig. 10 A, C4orf19 (chromosome 4 open reading frame 19) is broadly expressed across human cell types and tissues [ 42 ], with high protein levels in the kidney, liver, and GI tract [ 43 , 44 ] and while little is known about its function, an observed relationship between C4orf19 and colorectal cancer suggests that high expression levels might have some value as a marker for colorectal cancer [ 45 ], although elevated C4orf19 expression is also reported to show a favorable association with renal cancer survival [ 43 , 44 ]. Notably, four of the other proteins in this cluster (PDCD10, STK24, STK25, STK26) are known to associate into a complex with roles in maintaining epithelial integrity [ 46 , 47 ] and kidney water balance by regulating aquaporin trafficking and abundance in kidney tubule epithelial cells [ 48 ], suggesting a potential role for C4orf19 in normal kidney function.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Fig. 10 A, C4orf19 (chromosome 4 open reading frame 19) is broadly expressed across human cell types and tissues [ 42 ], with high protein levels in the kidney, liver, and GI tract [ 43 , 44 ] and while little is known about its function, an observed relationship between C4orf19 and colorectal cancer suggests that high expression levels might have some value as a marker for colorectal cancer [ 45 ], although elevated C4orf19 expression is also reported to show a favorable association with renal cancer survival [ 43 , 44 ]. Notably, four of the other proteins in this cluster (PDCD10, STK24, STK25, STK26) are known to associate into a complex with roles in maintaining epithelial integrity [ 46 , 47 ] and kidney water balance by regulating aquaporin trafficking and abundance in kidney tubule epithelial cells [ 48 ], suggesting a potential role for C4orf19 in normal kidney function.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Figure 8A , C4orf19 (chromosome 4 open reading frame 19) is broadly expressed across human cell types and tissues [35], with high protein levels in the kidney, liver, and GI tract [36][37] and while little is known about its function, an observed relationship between C4orf19 and colorectal cancer suggests that high expression levels might have some value as a marker for colorectal cancer [38], although elevated C4orf19 expression is also reported to show a favorable association with renal cancer survival [36][37]. Notably, four of the other proteins in this cluster (PDCD10, STK24, STK25, STK26) are known to associate into a complex with roles in maintaining epithelial integrity [39][40] and kidney water balance by regulating aquaporin trafficking and abundance in kidney tubule epithelial cells [41], suggesting a potential role for C4orf19 in normal kidney function.…”
Section: Resultsmentioning
confidence: 99%
“…Wang W. et al. reported that regulated C4ORF19 could promote colon adenocarcinoma cell proliferation, invasion, and migration ( 26 ). However, our understanding of the role of C4ORF19 in clear cell renal carcinoma is not clear so far.…”
Section: Discussionmentioning
confidence: 99%